1996
DOI: 10.1002/j.1460-2075.1996.tb01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of DNA base excision-repair with purified human proteins: interaction between DNA polymerase beta and the XRCC1 protein.

Abstract: Repair of a uracil‐guanine base pair in DNA has been reconstituted with the recombinant human proteins uracil‐DNA glycosylase, apurinic/apyrimidinic endonuclease, DNA polymerase beta and DNA ligase III. The XRCC1 protein, which is known to bind DNA ligase III, is not absolutely required for the reaction but suppresses strand displacement by DNA polymerase beta, allowing for more efficient ligation after filling of a single nucleotide patch. We show that XRCC1 interacts directly with DNA polymerase beta using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
509
1
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 707 publications
(529 citation statements)
references
References 40 publications
13
509
1
6
Order By: Relevance
“…23 Shen et al 11 reported 3 coding polymorphisms, i.e., Arg194Trp, Arg280His and Arg399Gln, in the XRCC1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…23 Shen et al 11 reported 3 coding polymorphisms, i.e., Arg194Trp, Arg280His and Arg399Gln, in the XRCC1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Soon thereafter, a stable complex of XRCC1 and LigIIIα was discovered [65] and by the late 1990s XRCC1 was established as a BER scaffold protein [66] in partnership with pol ß and PARP1 [16]. The list of cellular components that interact with XRCC1 has been expanded to include nicked DNA [67,68] and AP site containing DNA, both intermediates in the BER pathway [69].…”
Section: Scaffold Proteinsmentioning
confidence: 99%
“…Table I Possible entry mechanisms of a unified base excision repair model [12,17,23,63,66,75,88,113,119,128,129,149,150,[152][153][154][155][156][157] LigI…”
Section: Fig 2 a Unified Model Of Bermentioning
confidence: 99%
“…Studies continued to identify a role for pol β in the repair of damage induced by many different DNA damaging agents, including bleomycin [14,15] [21][22][23][24]. Several groups reported complete BER in vitro with pol β and additional purified proteins [22,23,25]. Although it was demonstrated in heterologous systems (E. coli and Saccharomyces cerevisiae) that pol β can conduct DNA replication and repair in vivo [26,27], it was not until a mouse gene knockout was made that the specificity of the repair conducted by pol β was defined [28].…”
Section: Dear Editormentioning
confidence: 99%